Perception and Significance of Basic Sciences for Clinical Studies - Motaz, Ahmed Abdelrahman NuggedAlla (International Journal of Human Anatomy, 2018)
Background: Faculty of Medicine and Health sciences at University of Kassala, Sudan was established 1990. It adopts the traditional curricula, which implemented in preclinical (basic sciences) and clinical phases. This study was held to explore students' perception and attitudes towards the basic sciences. Methods: A descriptive cross-sectional study was conducted during April- August 2017 among 251 medical students. Self-administered questionnaire was used to collect data. It was collected and analyzed using SPSS 16.0. Results: A total of 251 of participants in different phases of education in faculty of medicine and health sciences were included in the study; preclinical 116 (46.2%), 113 clinical (45.0%), and 22 (8.8%) were in internship. 95 (37.8 %) were males and 156 (62.2%) were females. The study revealed that physiology was the most preferable subject. Students' satisfaction to syllabus for anatomy, physiology and biochemistry was 61.4%, 43%, and 28.7% respectively. However, 46.6% of students spent a long time to understand biochemistry and 33.1% considered it as overloaded syllabus. Participants showed poor ability to link between theoretical and practical work in case of biochemistry (26.7%), where as anatomy and physiology were represented by 76.9% and 42.2% respectively. Less than half of students were able to integrate the subjects of basic sciences and basic with clinical sciences. Conclusion: In this study, the students determined the difficulties of recalling of information, poor integration between basic and clinical sciences and even integration within the subject. Development of integrated curriculum is necessary to improve the quality of education.
Keywords: Anatomy; Physiology; Attitude; Clinical Field; Students